The safety of blood flow restriction training as a therapeutic intervention for patients with musculoskeletal disorders: A systematic review - Minniti, M. C.; Statkevich, A. P.; Kelly, R. L.; Rigsby, V. P.; Exline, M. M.; Rhon, D. I.; Clewley, D. (The American Journal of Sports Medicine, 2020)
Background: The effectiveness of blood flow restriction training (BFRT) as compared with other forms of training, such as resistance training, has been evaluated in the literature in clinical and nonclinical populations. However, the safety of this intervention has been summarized only in healthy populations and not in clinical populations with musculoskeletal disorders.